Environmental change and the rate of phenotypic plasticity. (21st June 2022) - Burton, Tim; Ratikainen, Irja Ida; Einum, Sigurd
Abstract: With rapid and less predictable environmental change emerging as the 'new norm', understanding how individuals tolerate environmental stress via plastic, often reversible changes to the phenotype (i.e., reversible phenotypic plasticity, RPP), remains a key issue in ecology. Here, we examine the potential for better understanding how organisms overcome environmental challenges within their own lifetimes by scrutinizing a somewhat overlooked aspect of RPP, namely the rate at which it can occur. Although recent advances in the field provide indication of the aspects of environmental change where RPP rates may be of particular ecological relevance, we observe that current theoretical models do not consider the evolutionary potential of the rate of RPP. Whilst recent theory underscores the importance of environmental predictability in determining the slope of the evolved reaction norm for a given trait (i.e., how much plasticity can occur), a hitherto neglected possibility is that the rate of plasticity might be a more dynamic component of this relationship than previously assumed. If the rate of plasticity itself can evolve, as empirical evidence foreshadows, rates of plasticity may have the potential to alter the level predictability in the environment as perceived by the organism and thus influence the slope of the evolved reaction norm. However, optimality in the rate of phenotypic plasticity, its evolutionary dynamics in different environments and influence of constraints imposed by associated costs remain unexplored and may represent fruitful avenues of exploration in future theoretical and empirical treatments of the topic. We conclude by reviewing published studies of RPP rates, providing suggestions for improving the measurement of RPP rates, both in terms of experimental design and in the statistical quantification of this component of plasticity. Abstract : Individuals respond to environmental change via phenotypic plasticity, the magnitude of which is measured as the slope of the relationship describing phenotypic expression across environments (a). Yet, plasticity also takes time to manifest and the rate at which it occurs (b) might be as critical in enabling organisms to cope in new environments. However, we understand little about plasticity rates in an ecological or evolutionary context. By discussing why plasticity rates might evolve and providing guidelines for standard and comparable measurements, we hope to stimulate theoretical development and testing of novel hypotheses about organismal performance under environmental change.